Justification for the use of dietary supplements among pregnant women - Ivanović Nevena; Đorđević Brižita (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
Pregnancy is one of the most nutritionally demanding periods in a woman's life. During pregnancy there is an increase in nutritional requirements in order to support fetal growth and development. Maternal metabolic demands and tissue development specific to reproduction are also in a need for additional nutrition. Increased need for macro- and micronutrients can be achieved by well-balanced and varied diet. Dietary supplements may be used when it is not possible to have adequate diet due to subjective or objective reasons such as nausea and vomiting. Dietary supplements are defined as concentrated sources of nutrients and other substances with nutritional or physiological effect in pharmaceutical dosage forms. Supplements that are most commonly used in pregnancy are folic acid and iron. Substances that do not occur in sufficient amount in food, such as vitamins and minerals, polyunsaturated fatty acids n-3 series, diatary fibers, may also be added to a diet in a form of supplements. Different countries have different recommendations regarding use of dietary supplements in pregnancy, which indicates that the use of supplements largely depends on demographic, social and economic parameters. In Serbia, supplementation is based on recommendations from gynecologists and individual choice of a pregnant woman as there are still no national recommendations, except for supplementation of folic acid.